HUBUNGAN MUTU PELAYANAN KESEHATAN DENGAN KEPUASAN PASIEN RAWAT INAP PESERTA BPJS KESEHATAN DI RSUD SELASIH PANGKALAN KERINCI KABUPATEN PELALAWAN TAHUN 2015 - Marian Tonis; Ricky Wiranata Wiranata (Journal of Hospital Administration and Management, 2020)
Satisfaction is a key indicator of a standard health facility, which is a measure of patient care. Low patient satisfaction will have an impact on the number of visits that will affect provitabilitas health facilities. Based on data from hospitals selasih Pangkalan Kerinci, knowable Number bed Occupationcy Rate (BOR) in 2014 was 68.57%. The purpose of this study to determine Factors Associated With Care Inpatient Satisfaction Participants BPJS Healthcare In hospitals selasih Pangkalan Kerinci Pelalawan 2015. This research method is quantitative research design using cross sectional (cross-sectional) respondents are inpatients in June 2015. The entire sample of patients as many as 88 people, with sampling purposive sampling. The analysis is the analysis of univariate and bivariate with Chi-square test, measuring instruments used are questionnaires and using computerized data processing. The results were obtained with a tangible correlation between satisfaction in hospitals Selasih kerinci base with the results pvalue = 0.000 ≤ 0:05, there is a relationship reliability with satisfaction in hospitals selasih kerinci base with the results pvalue = 0.000 ≤ 0.05 responsiviness correlation with satisfaction in hospitals selasih base kerinci with the result pvalue = 0.000 ≤ 0:05, there is a relationship with the assurance of satisfaction in hospitals Selasih kerinci base with the results pvalue = 0.000 ≤ 0:05, there is a relationship of empathy with satisfaction in hospitals Selasih kerinci base with the results pvalue = 0.000 ≤ 0:05